Quad Fever in a Case of Cervical Cord Injury—A Rare Case Report - Ali, Sheena; Ganesan, Duraisamy; Sundaramoorthy, Varun (Asian Journal of Neurosurgery, 2022)
By definition, “quad fever” is an extreme elevation in body core temperature beyond 40.8°C (105.4°F) in a patient with spinal cord injury. This type of central nervous system hyperpyrexia is seen in spinal cord injury patients, particularly those with high cervical spine injury with quadriplegia. However, it has also been described in paraplegics with a mid- or higher level thoracic spine injury. The incidence of “quad fever” is rare, with the highest reported temperature being 44°C (111.2°F) with chronicled fatal outcomes.Though the use of antipyretics is generally efficacious, they are considerably ineffective in treating the hyperpyrexia seen in this type of severe central autonomic thermodysregulation.Here, we present a case of high cervical spine injury in a 24-year-old male. The trauma resulted in a C3–5 level cord contusion with incomplete quadriplegia (ASIA [American Spinal Cord Injury Association Impairment Scale] grade B). The patient developed high grade fever of 106°F within a week of admission postoperatively.Pancultures were negative and the wound was clean. Despite treatment with higher antibiotics and an infection disease specialist's consult, no obvious etiology was found. Drug-induced fever and thyroid function tests were excluded in other less-common causes.Based on the diagnosis of exclusion, “quad fever” was inferred as the cause. He had other signs of autonomic instability during the episodes such as bradycardia with hypotension.Our patient showed an almost early response to treatment to betablockers and antipsychotics after failure to respond to antibiotics, mechanical hypothermia, and antipyretics.
Keywords: hyperpyrexia; quad fever; thermodysregulation; spinal cord injury; neurogenic fever